A Comparison Of The Effects Of Pen-And-Paper And Email Dialogue Journal Writing On Writing Performance And Anxiety Among Tesl Undergraduates - Foroutan, Maryam (2009)

(untitled)
The purpose of this study was to compare the influence of two methods in writing dialogue journals, pen-and-paper as conventional tools, in contrast to e-mail as online tool, on writing performance in terms of content, language, vocabulary, language use and organization as well as writing anxiety. Measurement of writing performance was based on the ESL Composition Profile developed by Jacobs, Zinkgraf, Wormuth, Hartifel and Hughey (1981) and writing anxiety was measured by using the Second Language Writing Anxiety Inventory (SLWAI) from Cheng (2004). Forty two ESL students in their third semester took a course called “Computer Applications in TESL” participated in the study. Based on their expository writing grades obtained in the previous semester as well as race and gender; they were randomly assigned into two groups 1) e-mail dialogue journal writing and, 2) penand- paper dialogue journal writing. For the first session to obtain pre-test writing, all students were given topics to write and had to complete a pre-test writing anxiety questionnaire. Both groups received two different treatments. Participants in the e-mail dialogue journal group were asked to write dialogue journals to their secret pals by using e-mail while the participants in the pen-and-paper dialogue journal group, wrote their dialogues via pen and paper. Both groups kept corresponding dialogue journals in the class for a seven-week period. After going through seven weeks, post tests were conducted. All data were analyzed using SPSS to answer the hypotheses in the research. Independent-sample t-test and paired-sample t-test were utilized to compare two groups in terms of writing performance and writing anxiety. Results of the data analysis when two groups were compared showed that there is a significant difference between groups in terms of the overall writing performance and language use. However, the results for other components of writing performance; content, organization, vocabulary and mechanics as well as writing anxiety did not show statistically any significant difference between groups. The results for each group when pre and posttest overall writing performance were compared showed that there is a significant difference between groups i.e. participants in both groups have improved their writing performance due to using dialogue journals. Meanwhile, in terms of writing anxiety, paired sample t-test result showed there is no significant difference between pre and posttest writing anxiety for both groups.